Perceptions of the Role of West Virginia’s Cooperative Extension Service in Tobacco Control Coalitions - Reed, Donald; Lester, Dana; Danberry, Kathy; Fink, Peggy Lambert; Owens, Sherry (Frontiers in Public Health, 2016)
Despite the fact that the consequences of tobacco use are well identified and known, it remains to be the single most preventable cause of disease and death in the United States. In West Virginia the adult prevalence of cigarette smoking is currently at 26.8%. This study researches the perceptions of Cooperative Extension Service’s involvement and role in county level coalitions that address tobacco use in West Virginia. The research finding provide practical areas to increase the role of Extension Service in these vital efforts to save lives, reduce economic hardships on families, and reduce the healthcare burden to state government. Keyword List: Tobacco, Coalitions, West Virginia